Repressed Poles, Inhabitants of East and Southeast Lithuania: Their Return and Adaptation (1953–1964) - Stravinskienė, Vitalija (Genocidas ir rezistencija, 2014)
Using historiography and archival material, the article explores the adaptation of the Poles, who returned to the east and southeast of Lithuania, the factors which influenced and caused their adaptation; identifies the number of people who suffered reprisals of the Soviet government and who returned to this region of Lithuania. It also looks at their regional distribution and describes the activities used by the Soviet security forces to control Poles who were former political prisoners and deportees. The study covers the years 1953–1964, the so-called the “thaw” period, when the majority of the Lithuanian population that had been repressed by the Soviet government was released and returned to Lithuania or settled in the neighbouring republics. Their return and adaptation was very different. Adaptation of the Lithuanian population of Polish nationality was aggravated by registration restrictions in Vilnius and discontinued social relations, because after the war a lot of their friends, relatives or acquaintances left for Poland. Therefore, many of them took advantage of the renewed repatriation (1955–1959) from the USSR to Poland and using the opportunity moved from Lithuania to the neighbouring country.